CLASSROOM INTERACTION: AN ANALYSIS OF TEACHER TALK AND STUDENT TALK IN ENGLISH FOR YOUNG LEARNERS (EYL) - Rini Triani Pujiastuti (Journal of English and Education, 2013)
This research-based paper presents the investigation on 1) the realization of verbal classroom interaction, 2) types of teacher talk 3) teacher talk implication on student’s motivation, 4) student talk and 5) teacher’s roles in classroom interaction. Employing a qualitative research design and case study approach, the data for this study were collected in a classroom context where the participants were an English teacher for young leaners and her 15 studentsin one private primary school in Bandung in the form of observation and interview. The results indicate that all of the teacher talk categories of FIAC were revealed covering giving direction, lecturing, asking questions, using student’s ideas, praising, criticizing student’s behavior and accepting feelings. However, giving direction and lecturing were found as the most frequently used categories among all. In addition, the teacher mostly adopted a role as controller in the classroom as she frequently led the flow of interaction. In terms of student talk, student’s response and initiation were revealed in this study. It is also found that student’s initiation playsa significant part in the classroom interaction. Keywords: Classroom interaction, student talk, teacher talk, young learners.